A retrospective observational study of clinical profile, diagnosis, management and outcome of abdominal tuberculosis in 30 patients - Pancholi, Mukesh; Meena, Mahendra Kumar; Sharma, Praveen; Chaudhary, Devendra (International Surgery Journal, 2020)
Background: Abdominal tuberculosis is found worldwide although prevalence rates are still highest in the developing countries. The sites of involvement of abdominal tuberculosis are peritoneum, lymph nodes, intestine and solid viscera. The objectives of this study were to describe the clinical profile of patients with abdominal tuberculosis, to review the use of diagnostic modalities, both non-invasive and invasive and to study the outcome of management of abdominal tuberculosis. Methods: This is an observational retrospective study of 30 patients with diagnosis of abdominal tuberculosis treated at university linked teaching hospital of South Gujarat from August 2015 to November 2017. Results: In our study, disease was found almost equally prevalent in both rural and urban areas affecting mostly lower socio-economical class. The mean age was 34 years (range from 13 to 62); male and female ratio was 2.33:1; the mean hospital stay was 09 days (range from 5 to 48 days). Abdominal pain was present in almost all cases, having chronic pain in 21 patients and acute in 9 patients. There were 05 (16.7%) patients found to be HIV positive in this study. There was mortality of 02 patients post operatively due to sepsis in those patients operated in emergency with peritonitis. Conclusions: Abdominal tuberculosis is prevalent in lower socioeconomic class patients and affects younger male patients more commonly. Most commonly intestinal and mesenteric disease presented with chronic abdominal pain and constitutional symptoms of tuberculosis.